INCREASING TAX AWARENESS TO SUPPORT THE SUSTAINABILITY OF TOURISM BUSINESSES - Yoningsih, Kharisma Azmi; Orientani, Rezki; Hutami, Novita Uki; Khairun, Khairunnisa; Afgani, Rizky Rivaldi (Universitas Terbuka, 2025)
This study aims to enhance the understanding and awareness of taxation among tourism business actors through a descriptive qualitative approach based on community service activities involving resource persons from KPP Pratama Sumedang as well as related business actors and communities. Data were collected through documentation and participatory observation, then analyzed thematically to identify factors influencing tax compliance and their implications for the sustainability of tourism businesses. The results indicate that a comprehensive understanding of the benefits of taxation such as public infrastructure development, government subsidies, and business empowerment programs can improve the cooperative attitude of business actors in fulfilling their tax obligations. The main challenges identified are the low level of tax literacy and technical difficulties in tax reporting, which require a more intensive and continuous educational approach. Increased tax awareness is expected to strengthen tax contributions to state revenue, thereby supporting the development of higher-quality tourism infrastructure and the sustainability of businesses in this sector. This study recommends synergy between the government, educational institutions, and tourism communities to organize tax training tailored to the needs of business actors, in order to create an inclusive and sustainable tourism ecosystem.